Acute Headache Presentations to the Emergency Department: A Statewide Cross‐sectional Study. (January 2017) - Chu, Kevin H.; Howell, Tegwen E.; Keijzers, Gerben; Furyk, Jeremy S.; Eley, Robert M.; Kinnear, Frances B.; Thom, Ogilvie; Mahmoud, Ibrahim; Brown, Anthony F. T.
Abstract: Objectives: The objective of this study was to describe demographic and clinical characteristics including features that were consistent with subarachnoid hemorrhage (SAH), use of diagnostic tests, emergency department (ED) discharge diagnoses, and disposition of adult patients presenting with an acute headache to EDs statewide across Queensland, Australia. In addition, potential variations in the presentation and diagnostic workup between principal‐referral and city‐regional hospitals were examined. Methods: A prospective cross‐sectional study was conducted over 4 weeks in September 2014. All patients ≥ 18 years presenting to one of 29 public and five private hospital EDs across the state with an acute headache were included. The headache had to be the principal presenting complaint and nontraumatic. The 34 study sites attend to about 90% of all ED presentations statewide. The treating doctor collected clinical information at the time of the ED visit including the characteristics of the headache and investigations performed. A study coordinator retrieved results of investigations, ED discharge diagnoses, and disposition from state databases. Variations in presentation, investigations, and diagnosis between city‐regional and principal‐referral hospitals were examined. Results: There were 847 headache presentations. Median (range) age was 39 (18–92) years, 62% were female, and 31% arrived by ambulance. Headache peaked instantly in 18% and ≤ 1 hour in 44%. It was "worst ever" in 37%, 10/10 in severity in 23%, and associated with physical activity in 7.4%. Glasgow Coma Scale score was < 15 in 4.1%. Neck stiffness was noted on examination in 4.8%. Neurologic deficit persisting in the ED was found in 6.5%. A computed tomography (CT) head scan was performed in 38% (318/841, 95% CI = 35% to 41%) and an lumbar puncture in 4.7% (39/832, 95% CI = 3.4% to 6.3%). There were 18 SAH, six intraparenchymal hemorrhages, one subdural hematoma, one newly diagnosed brain metastasis, and two bacterial meningitis. Migraine was diagnosed in 23% and "primary headache not further specified" in 45%. CT head scans were more likely to be performed in principal‐referral hospitals (41%) compared to city‐regional hospitals (33%). The headache in patients presenting to the latter was less likely to be instantly peaking or associated with activity, but was no less severe in intensity and was more frequently accompanied by nausea and vomiting. Their diagnosis was more likely to be a benign primary headache. Variations in CT scanning could thus be due to differences in the case mix. The median (interquartile range) ED length of stay was 3.1 (2.2 to 4.5) hours. Patients was discharged from the ED or admitted to the ED short‐stay unit prior to discharge in 57 and 23% of cases, respectively. Conclusions: The majority of patients had a benign diagnosis, with intracranial hemorrhage and bacterial meningitis accounting for only 3% of the diagnoses. There are variations in the proportion of patients receiving CT head scans between city‐regional and principal‐referral hospitals. As 38% of headache presentations overall underwent CT scanning, there is scope to rationalize diagnostic testing to rule out life‐threatening conditions.